An Improved Anonymous Authentication Protocol for Wearable Health Monitoring Systems. (23rd April 2020) - Mo, Jiaqing; Shen, Wei; Pan, Weisheng
Abstract : Wearable health monitoring system (WHMS), which helps medical professionals to collect patients' healthcare data and provides diagnosis via mobile devices, has become increasingly popular thanks to the significant advances in the wireless sensor network. Because health data are privacy-related, they should be protected from illegal access when transmitted over a public wireless channel. Recently, Jiang et al. presented a two-factor authentication protocol on quadratic residues with fuzzy verifier for WHMS. However, we observe that their scheme is vulnerable to known session special temporary information (KSSTI) attack, privileged insider attack, and denial-of-service (DoS) attack. To defeat these weaknesses, we propose an improved two-factor authentication and key agreement scheme for WHMS. Through rigorous formal proofs under the random oracle model and comprehensive informal security analysis, we demonstrate that the improved scheme overcomes the disadvantages of Jiang et al.'s protocol and withstands possible known attacks. In addition, comparisons with several relevant protocols show that the proposed scheme achieves more security features and has suitable efficiency. Thus, our scheme is a reasonable authentication solution for WHMS.